Effect of Selected Drying Methods on the Cannabinoid Profile of Cannabis sativa L. var. sativa Inflorescences and Leaves - Joanna Kanabus; Marcin Bryła; Marek Roszko (Polish Journal of Food and Nutrition Sciences)
The hemp industry uses traditional drying methods based on ambient temperature. However, these methods do not guarantee a high-quality dried product due to the possibility of mold growth. The present study aimed to evaluate the effect of the drying method for parts of the Cannabis sativ a L. var. sativa plant (ambient temperature drying without light, freeze-drying, and convective drying at 50, 60, and 70°C) on the content of 17 cannabinoids. The leaves were separated, and the inflorescences were subdivided according to size. Analyses were performed using UHPLC-HESI-MS. Traditional drying of the inflorescences increased the total cannabinoid content to 17.608–22.209 mg/g DM relative to fresh material (8.562–11.386 mg/g DM). Increasing the drying temperature by 10°C significantly enhanced cannabinoid degradation in the dried inflorescences. The most significant increase in cannabidiol and Δ 9 -tetrahydrocannabinol content in the inflorescences was observed during traditional drying (up to 10 times). The greatest decrease in the content of the main acid precursors of cannabinoids, i.e. , cannabidiolic acid and Δ 9 -tetrahydrocannabinolic acid A, was observed during convective drying (up to 3 times). The present study is one of the first to compare the effects of drying methods on the profile of cannabinoids in selected parts of the Cannabis sativa L. plant.